JUMPA Vol.2 No.1 Feb 2015 ANALISA RASIO KEUANGAN YANG MEMENGARUHI PERINGKAT OBLIGASI PERUSAHAAN MANUFAKTUR: ANALISA RASIO KEUANGAN YANG MEMENGARUHI PERINGKAT OBLIGASI PERUSAHAAN MANUFAKTUR - Gunawan Trisakti School of Management Jakarta; Tita Deitiana Trisakti School of Management Jakarta (Jurnal Manajemen dan Perbankan (JUMPA), 2015)
The purpose of this research is to test and investigate the influence of return on equity, net profit margin, current ratio, long term liabilities to total assets and total asset turnover towards bond ratings. The population of this research is manufacturing companies listed in the Indonesia Stock Exchange over the 5 years period 2008-2012. Samples consist of 9 manufacturing companies, selected using purposive sampling method. The data type is secondary data which collected from Indonesia Stock Exchange. Data was analyzed using ordinal logistic regression (ordered logit). The result shows that return on equity, long term liabilities to total assets and total asset turnover have influences towards bond ratings. Otherwise, net profit margin and current ratio do not have influences towards bond ratings.